Przestrzeń w twórczości Olgi Tokarczuk - Fliszewska, Olga (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
The article presents and analyses types of space existing in the literary output of Olga Tokarczuk. The author focuses on exploring two triple divisions of this phenomenon. First division deals with an area understood as both open and closed sites, and objects. The second division distinguishes realistic space (specific events and places), internal (a hero’s psychology and a relationship between a human being and a place) and mythical (placing reality in myth).